An examination of smart growth: a case study of New Columbia in Portland, Oregon - Dikeman, Stephanie L. (Kansas State University, 2009)
Smart growth has been offered as one potential solution to ease the strain that urban sprawl creates on cities from a social, economical, and environmental perspective. Simply put, smart growth means making smart decisions on the development and redevelopment of our aging cities. During a site visit to the low income housing community of New Columbia. Located in Portland, Oregon, a scorecard was used to analyze the smart growth components of the development. The scorecard had a maximum of 78 points and New Columbia received 73.5 points. Based on the scorecard rating, New Columbia appears as though it is meeting, and often times exceeding, almost all of the smart growth principles. It has successfully provided a mix of uses, a range of housing options (both price and style), enhances community character through design, is compact and transit-oriented, provides open space and supports environmental protection. This report serves as an analysis of New Columbia in Portland, Oregon, to determine if the initial intentions of the smart growth approach are truly being met four years after the completion of the project.
Keywords: Smart Growth; Scorecard Examination; Portland, Oregon; New Columbia; Urban and Regional Planning (0999)